Noncooperative Dynamic Game Model between Drivers and Crossing Pedestrians. (January 2015) - Cheng, Guozhu; Liu, Botong; Wu, Lixin; Fang, Qingheng; Yu, Ke
In China, unsignalized crosswalks lead to the increasing ofconflicts between vehicles and crossing pedestrians. In this paper, the relationships of risks perceived by drivers, crossing pedestrians, and vehicle speed were revealed through a decision-making risk experiment. The model of collision risk probability was established by using probability theory. Then the strategy spaces, the payoff function, and payoff matrix were given. The model of dynamic noncooperative game between the drivers and crossing pedestrians was established. In addition, the equilibrium solutions of the model were analyzed as well. The results of analysis shows that the crossing state is the best decision for pedestrians and drivers should keep uniform speed or accelerate when vehicle speed is low. At medium speed, there is no clear difference between waiting and crossing state for pedestrians. Actually, the crossing state is better than waiting state. For drivers, there is no evident difference among acceleration, deceleration, and keeping uniform speed of vehicles, but the better choice is keeping uniform speed of vehicles. At high speed, pedestrians should not cross because of there are high risks. Therefore, the best solution is that the drivers keep uniform speed of vehicles.